Pengaruh Promosi Media Sosial, Citra Destinasi Dan Fasilitas Terhadap Minat Berkunjung Kembali Kebun Raya Mangrove Wonorejo Kota Surabaya - Agung, Ananda Kusuma; Fianto, Achmad Yanu Alif (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Interest in visiting ecotourism destinations is a manifestation of consumer decisions influenced by various external stimuli. Wonorejo Mangrove Botanical Garden in Surabaya faces significant challenges in the form of fluctuating visitor numbers, with data from 2024 and 2025 showing unstable trends. This study aims to analyze and empirically test the influence of social media promotion, destination quality, and the physical form of facilities on tourists' interest in visiting, both partially and simultaneously. The research method employed is quantitative with a survey approach involving 100 respondents selected through accidental sampling. Primary data were collected via Likert-scale questionnaires and analyzed using multiple linear regression with SPSS software assistance. The research results indicate that social media promotion has a positive and significant effect on visit intention, where visual content such as reels serves as a strong trigger for potential tourists. Destination quality, encompassing aspects of attractions, accessibility, and services, also proves to make a substantial contribution to forming positive visitor perceptions. Additionally, the physical form of facilities such as toilet cleanliness, jogging track conditions, and gazebo availability emerges as a crucial factor determining comfort and visit interest. Simultaneously, all three variables significantly influence interest in visiting Wonorejo Mangrove Botanical Garden. These findings underscore the importance for managers to revitalize deteriorating physical facilities and optimize digital communication strategies to ensure the sustainability of ecotourism in the future.